2013
DOI: 10.1186/1472-6963-13-492
|View full text |Cite
|
Sign up to set email alerts
|

Healthier choices in an Australian health service: a pre-post audit of an intervention to improve the nutritional value of foods and drinks in vending machines and food outlets

Abstract: BackgroundVending machines and shops located within health care facilities are a source of food and drinks for staff, visitors and outpatients and they have the potential to promote healthy food and drink choices. This paper describes perceptions of parents and managers of health-service located food outlets towards the availability and labelling of healthier food options and the food and drinks offered for sale in health care facilities in Australia. It also describes the impact of an intervention to improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(64 citation statements)
references
References 6 publications
3
59
1
1
Order By: Relevance
“…This research is consistent with international audits that have found that vending machines contribute to unhealthy food environments . Research spanning the past three decades has shown that vending machines on campuses have been a source of unhealthy options, and offerings have been found to be high in fat, sugar and energy and low in fibre .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This research is consistent with international audits that have found that vending machines contribute to unhealthy food environments . Research spanning the past three decades has shown that vending machines on campuses have been a source of unhealthy options, and offerings have been found to be high in fat, sugar and energy and low in fibre .…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, our results are likely to be generalisable to other tertiary institutions given that these institutions use the same large vending companies and procurement systems as in the audited university. The product range described in the current study reflects vending machines’ stocks across the country . The audit for some vending machines was conducted over two time periods; however, our test–retest data of the majority of machines (80%) demonstrated that vending machine contents remained static, and seasonal variation did not influence the results of machines compared between the two time points.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Vending machines are widely distributed and can be found in workplaces, schools, universities and hospitals . A recent Australian study reported that the foods and beverages sold in vending machines at train stations are predominantly of minimal nutritional value .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Vending machines are widely distributed and can be found in workplaces, schools, universities and hospitals. 9,10 A recent Australian study reported that the foods and beverages sold in vending machines at train stations are predominantly of minimal nutritional value. 9 Several studies at schools, hospitals and train stations showed that products vended were mainly chips, chocolate, confectionary, soft drinks, sport drinks and energy drinks, 11,12 which were generally high in energy, sugar and salt.…”
Section: Introductionmentioning
confidence: 99%